2009
DOI: 10.1261/rna.1747509
|View full text |Cite
|
Sign up to set email alerts
|

Do conformational biases of simple helical junctions influence RNA folding stability and specificity?

Abstract: Structured RNAs must fold into their native structures and discriminate against a large number of alternative ones, an especially difficult task given the limited information content of RNA's nucleotide alphabet. The simplest motifs within structured RNAs are two helices joined by nonhelical junctions. To uncover the fundamental behavior of these motifs and to elucidate the underlying physical forces and challenges faced by structured RNAs, we computationally and experimentally studied a tethered duplex model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 42 publications
3
68
0
Order By: Relevance
“…1A). Once aligned, particular tertiary partners can interact and thereby provide stabilization of intermediate and folded states (25)(26)(27)30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Once aligned, particular tertiary partners can interact and thereby provide stabilization of intermediate and folded states (25)(26)(27)30).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent experiments demonstrated conserved orientation preferences for these and other junctions when placed in different RNAs, suggesting the transferability of junction-stacking properties (19,25). More recently, it has been suggested that RNA substructures of two helices of defined lengths spanned by junctions of various topologies are basic building blocks of RNA tertiary structure; these substructures are referred to generically as helix-junction-helices (HJHs) (26)(27)(28).…”
Section: Significancementioning
confidence: 99%
“…RNA secondary is preformed and stable, and RNA tertiary contact partners come together due to diffusion of the RNA helices they are embedded in (66,104,109). RNA tertiary contact formation also typically requires local unfavorable conformational rearrangements (104,(110)(111)(112)(113)(114)(115) such that the rates of formation of these interactions are orders of magnitude slower than diffusional collision (104,116).…”
Section: Discussionmentioning
confidence: 99%
“…For example, junctions (linkers) limit the conformations of unfolded states (52)(53)(54) and can be rigidified by Mg 2þ . In support of this, the [Mg 2þ ]-dependent decrease in the entropic cost of TL-R docking is much more pronounced in the A 7 vs. U 7 constructs (Tables 1 and 2)-suggesting that [Mg 2þ ]-dependent rigidification of the linker is of large entropic benefit to the docking process.…”
Section: Discussionmentioning
confidence: 99%